2018
DOI: 10.6004/jadpro.2018.9.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload in Myelodysplastic Syndromes: Pathophysiology, Consequences, Diagnosis, and Treatment

Abstract: Myelodysplastic syndromes (MDS) are a heterogeneous group of hematologic neoplasms varying in severity affecting one or more lines of hematopoiesis. Ineffective erythropoiesis results in dysregulation of iron metabolism. Most MDS patients have anemia, and some require regular red blood cell transfusions. These transfusions, in addition to factors of the disease itself, can result in iron overload (IO). Retrospective analyses suggest that MDS patients with IO have reduced overall survival and poorer outcomes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…ERFE expression was increased in all MDS subtypes compared to healthy controls, but was specifically pronounced in cases with ring sideroblasts (MDS-RS-SLD and MDS-RS-MLD). This data is in line with the observation that MDS-RS patients already present with elevated levels of ferritin before they become transfusion dependent ( 16 ).…”
Section: Increased Levels Of Erfe In Mds With Ring Sideroblastssupporting
confidence: 91%
“…ERFE expression was increased in all MDS subtypes compared to healthy controls, but was specifically pronounced in cases with ring sideroblasts (MDS-RS-SLD and MDS-RS-MLD). This data is in line with the observation that MDS-RS patients already present with elevated levels of ferritin before they become transfusion dependent ( 16 ).…”
Section: Increased Levels Of Erfe In Mds With Ring Sideroblastssupporting
confidence: 91%
“…Therefore, other signals or cells within the bone microenvironment or beyond may participate in this regulation. In line with this, it has been shown that FGF-23 production/cleavage can be triggered by erythropoietin, iron deficiency, anemia, and inflammation [8][9][10], factors that also play a role in MDS [11,12]. While iron serum levels are unchanged in NHD13 mice, erythropoietin is upregulated.…”
mentioning
confidence: 86%
“…Blood transfusions remain the dominant cause of iron overload in MDS patients. 44,45 Especially for patients suffering from lowrisk or intermediate-1-risk MDS, the improvement of anemia through RBC transfusions is a central point of supportive care. 7 Iron overload can develop rapidly as every unit of transfused blood contains about 200 to 250 mg of iron, whereas natural iron losses reach only 1 to 2 mg daily.…”
Section: Chronic Transfusionsmentioning
confidence: 99%
“…Blood transfusions remain the dominant cause of iron overload in MDS patients 44,45 . Especially for patients suffering from low‐risk or intermediate‐1‐risk MDS, the improvement of anemia through RBC transfusions is a central point of supportive care 7 .…”
Section: Iron Homeostasis and Pathology Of Iron Overload In Mdsmentioning
confidence: 99%
See 1 more Smart Citation